2023
DOI: 10.1002/sres.2971
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐stakeholder structured dialogues: Five generations of evolution of dialogic design

Yiannis Laouris,
Kevin Dye

Abstract: The paper reviews the evolution of Interactive Management, later referred to as Structured Democratic Dialogue, starting from the early 1970s up to this date. The authors propose a generational classification scheme consisting of five periods based primarily on whether some or all stages of the process were implemented synchronously or asynchronously and whether the participants' presence was physical, virtual or hybrid. Other aspects such as modifications in the steps of the process; the evolution of the soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Laouris, Dye, Michaelides and Christakis (2014) indicate how the co-laboratories of democracy offer choices for designing sustainable futures. Laouris and Dye (2023) for their part provide an account (from their perspective) of developments in SDD since its inception. Laouris and Romm (2022b) offer their proposal for why SDD must be recognized as a problem structuring method.…”
Section: The Structuring Of the Articlementioning
confidence: 99%
“…Laouris, Dye, Michaelides and Christakis (2014) indicate how the co-laboratories of democracy offer choices for designing sustainable futures. Laouris and Dye (2023) for their part provide an account (from their perspective) of developments in SDD since its inception. Laouris and Romm (2022b) offer their proposal for why SDD must be recognized as a problem structuring method.…”
Section: The Structuring Of the Articlementioning
confidence: 99%
“…It has been shown through crowdsourcing experiments that an averaged model from a larger sample of individuals performs worse than one constructed from a smaller sample Aminpour et al (2020). Several scientists and, in particular, the teams of John Warfield (1976Warfield ( , 1994Warfield ( , 1995Warfield & Cardenas, 1994), Aleco Christakis (Christakis & Bausch, 2006;Flanagan & Christakis, 2010) and Yiannis Laouris (Laouris, 2012Laouris & Christakis, 2007;Laouris et al, 2008a;Laouris & Romm, 2022a, 2022bLaouris, 2022aLaouris, , 2022bLaouris & Dye, 2023;Laouris & Metcalf, 2023;Laouris & Romm, 2022a;Michaelides & Laouris, 2023) have developed and refined systemic methodologies towards this goal. The authors' extended network has demonstrated how harnessing collective wisdom can be instrumental in: rendering our world more accessible (Laouris et al, 2008b;Laouris et al, 2017;Roe et al, 2011); sustainable (Ferri et al, 2018;; reinventing education (Laouris et al, 2010) and democracy (Laouris & Romm, 2022a, 2022bLaouris et al, 2022;Romm et al, 2022); resolvinginter-communal conflicts (Laouris et al, 2009a(Laouris et al, , 2009b; or reforming local governance (Laouris & Michaelides, 2018;Michaelides & Laouris, 2023).…”
Section: From Individual To Collective Wisdommentioning
confidence: 99%
“…They use the emerging consensus to design more effective plans to reform the socio-technical systems the group wishes to improve. More recently, they attempted to scale up the process using hybrid face-to-face and virtual or asynchronous processes (Laouris, 2022a(Laouris, , 2022bLaouris & Christakis, 2007;Laouris & Dye, 2023;Laouris & Metcalf, 2023). The Institute for 21st Century Agoras (2022) operates as a global coordinating body for systems scientists involved in the theory and practice of Dialogic Design Science, a branch of operations research and complex systems science.…”
Section: Introductionmentioning
confidence: 99%